TrkB Truncated Isoform Receptors as Transducers and Determinants of BDNF Functions - Tessarollo, Lino; Yanpallewar, Sudhirkumar (Frontiers in Neuroscience, 2022)
Brain-derived neurotrophic factor (BDNF) belongs to the neurotrophin family of secreted growth factors and binds with high affinity to the TrkB tyrosine kinase receptors. BDNF is a critical player in the development of the central (CNS) and peripheral (PNS) nervous system of vertebrates and its strong pro-survival function on neurons has attracted great interest as a potential therapeutic target for the management of neurodegenerative disorders such as Amyotrophic Lateral Sclerosis (ALS), Huntington, Parkinson’s and Alzheimer’s disease. So far, BDNF-based clinical trials for ALS have failed probably due to poor pharmacodynamics and pharmacokinetics. The TrkB gene, in addition to the full-length receptor, encodes a number of isoforms, including some lacking the catalytic tyrosine kinase domain. Importantly, one of these truncated isoforms, namely TrkB.T1, is the most widely expressed TrkB receptor in the adult suggesting an important role in the regulation of BDNF signaling. Although some progress has been made, the mechanism of TrkB.T1 function is still largely unknown. Here we critically review the current knowledge on TrkB.T1 distribution and functions that may be helpful to our understanding of how it regulates and participates in BDNF signaling in normal physiological and pathological conditions.